FILM â€œDEATHNOTE THE FIRST NAMEâ€ KARYA TSUGUMI OHBA DALAM PERSPEKTIF SEMIOTIKA CHARLES SANDERS PIERCE - Rudiyanto, Fais; Darmawan, Arif; Jupriono, Jupriono (representamen, 2015)
This film begins when Light Yagami finds a book that turned out to belong to a Shinigami (God ofDeath) named Ryuk (Ryuku). In the Death Note Ryuk owned, there are ways to use the Death Notewritten by him alone. Death Note is then used to realize his ideals is to create a clean new world of crime,with himself as a god, by writing the name of the perpetrator into Deathnote book, the offender will dieinstantly in 40 seconds in this study researchers with the theme or topic of fanaticism exist in a moviewith the title "the First Name Deathnote". Purpose of this research was to determine and analyze themeaning of the film, the message of social and moral student named Light Yagami and L in the filmDetective Deathnote The First Name. This research method is a method of semiotic analysis withqualitative descriptive research with interpretive paradigm. The object of research is a Light That aMurderer (KIRA) through symbols Deathnote message in the film The First Name. The results of thisstudy indicate bahwapemuda named Light Yagami Having high ideals to create a new world in whichthere is no crime, denggan using Light Deathnote book can kill all the people who are consideredunworthy of life in the world because of his criminal actions. The suggestion of this research for the filmobserver especially moviegoers are expected not to imitate him Light, which tends to have the ambition tobe the god of the world's poor, as well as showing the inability of the police in dealing with crime. Thisstudy expects that the police are doing a good job and should provide just punishment for the crime.Key words: film, symbolic communication, semiotics analysis, moral, social messaging